Use of ultrasonic extraction in determining apparent digestibility in fish feed - Cavecci, Bruna [UNESP]; de Lima, Paula Monteiro [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira [UNESP]; de Queiroz, João Vitor [UNESP]; Bittarello, Alis Correia [UNESP]; de Padilha, Pedro Magalhães [UNESP] (Springer Nature, 2015)
The feeds supplied to farmed fish should be rich in protein and minerals, such as animal protein, but more expensive alternatives comprising vegetable protein have emerged in recent years. However, the minerals essential to the proper development of fish must be assessed. To determine whether the minerals supplied in the diet are being fully exploited, the equation of the apparent digestibility coefficient is typically used with an external marker such as chromium. Moreover, the concentrations of the metals of interest are usually obtained using an acid digestion in the digester block; however, this digestion is harmful to both the analyst and the environment. An alternative to this digestion is described in this work. Four types of feeds were made with different types of protein substitutes.
Keywords: Aquaculture; Extraction of minerals; Nutrients; Oreochromis niloticus